BLOOD MEASURES IN PATIENTS WITH COVID-19 (Spectrum Journal of Innovation, Reforms and Development, 2023)
Сoronavirus infection mainly affects the respiratory tract, but according to the latest information, COVID-19 is a systemic disease, affecting the respiratory, cardiovascular, gastrointestinal, urinary, neurological, hematopoietic and immune systems. Purpose of research is evaluation of blood and urine analysis. Research material on COVID-19 with 200 sick patients. Research methods: general blood analysis. The degree of leukocytosis, neutrophilia and lymphocytopenia depends on the extent to damage the lungs in coronavirus infection.